1999
DOI: 10.1164/ajrccm.159.2.9802093
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis Stimulates Nitric Oxide Production and Lung Damage in Rats

Abstract: Systemic hypotension during sepsis is thought to be due to nitric oxide (NO) overproduction, but it may also be due to acidosis. We evaluated in healthy rats the consequences of acid infusion on NO and blood pressure. Sprague-Dawley rats were anesthetized, and ventilated with room air. The animals were randomized into four groups. Group 1 (C, n = 10) received only normal saline at rates comparable to the other groups. Group 2 (A1, n = 10) received hydrochloric acid at 0.162 mmol in the first 15 to 30 min, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
3
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 34 publications
7
81
3
4
Order By: Relevance
“…However, the paradox in which mild and severe acidosis induced by HCl results in opposite effects on NO has not been satisfactorily explained. Pedoto and colleagues (29) suggested that the optimal intracellular pH (pH i ) for iNOS is near 7.0 and that the addition of acid would lower pH i toward the optimal value, thus increasing iNOS activity and NO production. Further addition of acid would cause pH i to fall below the optimal value, leading to a decrease in NO production (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the paradox in which mild and severe acidosis induced by HCl results in opposite effects on NO has not been satisfactorily explained. Pedoto and colleagues (29) suggested that the optimal intracellular pH (pH i ) for iNOS is near 7.0 and that the addition of acid would lower pH i toward the optimal value, thus increasing iNOS activity and NO production. Further addition of acid would cause pH i to fall below the optimal value, leading to a decrease in NO production (29).…”
Section: Discussionmentioning
confidence: 99%
“…Pedoto and colleagues (29) suggested that the optimal intracellular pH (pH i ) for iNOS is near 7.0 and that the addition of acid would lower pH i toward the optimal value, thus increasing iNOS activity and NO production. Further addition of acid would cause pH i to fall below the optimal value, leading to a decrease in NO production (29). This hypothesis was recently tested by Huang et al (14), who demonstrated that the optimal pH o for NO formation by iNOS was 7.2 in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lung MPO was assessed as an index of PMN numbers (30). Briefly, whole unlavaged lungs were homogenized in 2 ml of 50 mM KH 2 PO 4 , pH 7.4, and centrifuged, and the supernatant was discarded.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, exhaled NO was significantly correlated with carbon monoxide diffusing capacity of the lungs (DL,CO) and was independent of inhaled corticosteroid therapy [118]. Acidosis is frequently associated with exacerbations of COPD and may have a direct vasodilatory influence on the systemic vasculature, and lead to increased NO production, and myeloperoxidase activity in lung [119]. In fact, in an acidic environment, the reaction between NO and oxygen radicals becomes further enhanced, leading to more tissue damage [120].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%